Karl Außerhofer - Das Kriegstagebuch eines Soldaten im Ersten Weltkrieg - Wisthaler, Sigrid (alpine space - man and environment, 2010)
The diary of Karl Außerhofer, written during World War I, reports on his military service in the mountains near Pustertal (Val Pusteria)and at the southern frontline. It shows his personal perception and of the enemies. Emotional insights are paired with the life of his family backed by the hope for a better future. Comment on countryside, weather, food, leisure, clothing, hygiene, housing, illness, death, and religion complete this very personal report. This publication includes the litteral transcription of the original diary complemented by contentual and linguistic commentaries.